Marine Heatwaves and Their Depth Structures on the Northeast U.S. Continental Shelf - Großelindemann, Hendrik; Ryan, Svenja; Ummenhofer, Caroline C.; Martin, Torge; Biastoch, Arne (Frontiers in Climate, 2022)
Marine Heatwaves (MHWs) are ocean extreme events, characterized by anomalously high temperatures, which can have significant ecological impacts. The Northeast U.S. continental shelf is of great economical importance being home to a highly productive ecosystem. Local warming rates exceed the global average and the region experienced multiple MHWs in the last decade with severe consequences for regional fisheries. Due to the lack of subsurface observations, the depth-extent of MHWs is not well known, which hampers assessing impacts on pelagic and benthic ecosystems. This study utilizes a global ocean circulation model with a high-resolution (1/20°) nest in the Atlantic to investigate the depth structure of MHWs and associated drivers on the Northeast U.S. continental shelf. It is shown that MHWs exhibit varying spatial extents, with some only occurring at depth. Highest intensities are found around 100m depth with temperatures exceeding the climatological mean by up to +7°C, while surface intensities are typically smaller (around +3°C). Distinct vertical structures are associated with different spatial MHW patterns and drivers. Investigation of the co-variability of temperature and salinity reveals that over 80% of MHWs at depth (>50m) coincide with extreme salinity anomalies. Two case studies provide insight into opposing MHW patterns at the surface and at depth, being forced by anomalous air-sea heat fluxes and Gulf Stream warm core ring interaction, respectively. The results highlight the importance of local ocean dynamics and the need to realistically represent them in climate models.